2018
DOI: 10.1039/c8dt03312a
|View full text |Cite
|
Sign up to set email alerts
|

Post-synthetic modification of zirconium metal–organic frameworks by catalyst-free aza-Michael additions

Abstract: UiO-66-NH2 reacts with acrylonitrile, acrylic acid, methyl acrylate and methyl vinyl ketone leading to post-synthetic modification of the MOF through C–N bond formation. The acrylonitrile-modified MOF undergoes further reaction to form a tetrazolate-modified MOF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 43 publications
(55 reference statements)
0
11
0
Order By: Relevance
“…For example, one of the most widely studied post-synthetic reactions in Zr-MOFs is covalent modifications at the pendant amino units with various substrates including aziridines, acid anhydrides, and aldehydes in functionalized Zr-MOFs. [136][137][138] Another way to efficiently engineer a pore environment with controllable loadings of functional groups is through click reactions, such as copper-catalyzed azide-alkyne cycloaddition (CuAAC) and inverse-electron demand Diels-Alder (iEDDA) reactions (Figure 9B). [139][140][141][142] Quantitative CuAAC reactions can be utilized to place varying functional groups with controlled loading and density in MOFs through the reaction of azide groups and alkynes, while iEDDA reactions, widely applied in bioconjugate chemistry, allow for a mild and fast pore modification in MOFs through the reaction between tetrazine groups and alkenyl-based compounds.…”
Section: Reviewmentioning
confidence: 99%
“…For example, one of the most widely studied post-synthetic reactions in Zr-MOFs is covalent modifications at the pendant amino units with various substrates including aziridines, acid anhydrides, and aldehydes in functionalized Zr-MOFs. [136][137][138] Another way to efficiently engineer a pore environment with controllable loadings of functional groups is through click reactions, such as copper-catalyzed azide-alkyne cycloaddition (CuAAC) and inverse-electron demand Diels-Alder (iEDDA) reactions (Figure 9B). [139][140][141][142] Quantitative CuAAC reactions can be utilized to place varying functional groups with controlled loading and density in MOFs through the reaction of azide groups and alkynes, while iEDDA reactions, widely applied in bioconjugate chemistry, allow for a mild and fast pore modification in MOFs through the reaction between tetrazine groups and alkenyl-based compounds.…”
Section: Reviewmentioning
confidence: 99%
“…The UiO-66-NH 2 has the formula Zr 6 O 4 (OH) 4 (BDC-NH 2 ) 6 with a molecular weight of 1760.1 g/mol. 67 Considering that there are 12 COO in one UiO-66 unit, there will be 12 H addition if all carboxylate groups are hydrogenated. The numbers lead to about 0.68 wt % hydrogen adsorption, which basically agrees with our maximum observation.…”
Section: Inductively Coupled Plasma Mass Spectrometry (Icp-ms) Icp-ms...mentioning
confidence: 99%
“…UiO-66 and its analogues are stable in acids, so cannot be digested in the same way as IRMOFs. Instead, samples were digested using aqueous ammonium fluoride solution, 28 and analysed, following digestion, by 1 H NMR spectroscopy. The analysis revealed that the sample had included 35.1 wt% 3-octanone so UiO-66-NHPr exhibits a lower capacity than IRMOF-NHPr using neat 3-octanone.…”
Section: Dalton Transactions Communicationmentioning
confidence: 99%